2019
DOI: 10.1002/pds.4920
|View full text |Cite
|
Sign up to set email alerts
|

The role of prescription drugs in female overactive bladder syndrome—A population‐wide cohort study

Abstract: Purpose: Overactive bladder (OAB) syndrome has severe effects on quality of life.Certain drugs are known risk factors for OAB but have not been investigated in a population-wide cohort. The objective of this study was to investigate the role of prescription drugs in the etiology of the OAB.Methods: Retrospective cohort study using a population-wide database of 4 185 098 OAB-naïve women followed Strengthening the Reporting of Observational Studies in Epidemiology guidelines. We investigated the subscription use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The etiology of OAB has been shown to be associated with age, obesity, DM, cardiac disorders, pelvic organ prolapse, parity and drug use. (6,13,(22)(23)(24) In this study, the OAB-V8 score was compared with age, weight, height, BMI, hip circumference, waist circum- 13) In this study, the OAB-V8 score was observed to increase with age. The mean OAB-V8 score below 45 years was 6.33, while above 45 years it was 9.51 and there was a significant difference (p<0.005).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The etiology of OAB has been shown to be associated with age, obesity, DM, cardiac disorders, pelvic organ prolapse, parity and drug use. (6,13,(22)(23)(24) In this study, the OAB-V8 score was compared with age, weight, height, BMI, hip circumference, waist circum- 13) In this study, the OAB-V8 score was observed to increase with age. The mean OAB-V8 score below 45 years was 6.33, while above 45 years it was 9.51 and there was a significant difference (p<0.005).…”
Section: Discussionmentioning
confidence: 85%
“…Studies have shown that demographic features like age, obesity and parity (6) and laboratory parameters like diabetes mellitus (DM) and hyperlipidemia (7)(8) are associated with OAB. A strong relation was detected especially between obesity and OAB(9,10) but there is no study on obesity type in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation